Huntingtin processing in pathogenesis of Huntington disease - QIN Zheng-hong; GU Zhen-lun (Acta Pharmacologica Sinica; Vol 25, No 10 (October 2004): Acta Pharmacologica Sinica, 2016)
Huntingtons disease (HD) is caused by an expansion of the polyglutamine tract in the protein named huntingtin. The expansion of polyglutamine tract induces selective degeneration of striatal projection neurons and cortical pyramidal neurons. The bio-hallmark of HD is the formation of intranuclear inclusions and cytoplasmic aggregates in association with other cellular proteins in vulnerable neurons. Accumulation of N-terminal mutant huntingtin in HD brains is prominent. These pathological features are related to protein misfolding and impairments in protein processing and degradation in neurons. This review focused on the role of proteases in huntingtin cleavage and degradation and the contribution of altered processing of mutant huntingtin to HD pathogenesis.